2022
DOI: 10.55559/sjahss.v1i08.41
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in Second Language in Relation to Students’ Speaking Performance

Abstract: Language anxiety is thought to hinder language learning, and if the learners are truly anxious in class, they are probably not fully engaged, if at all. With the help of the Foreign Language Speaking Anxiety Scale (FLSAS) and a free-speaking exercise, this study intends to ascertain the association between language anxiety and speaking performance among undergraduate and graduate students. Frequency count, percent, mean, and Kruskal Wallis were used as statistical techniques to total, tabulate, and further ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, it can be found in interviews and diaries that the online environment can alleviate students' communication anxiety because students "don't have to" when answering questions. Stand up, and you don't have to face the gaze of teachers and classmates," thereby reducing students' stress and anxiety (Robinson, 2001;Daymiel, 2022).…”
Section: Environmental Factorsmentioning
confidence: 99%
“…However, it can be found in interviews and diaries that the online environment can alleviate students' communication anxiety because students "don't have to" when answering questions. Stand up, and you don't have to face the gaze of teachers and classmates," thereby reducing students' stress and anxiety (Robinson, 2001;Daymiel, 2022).…”
Section: Environmental Factorsmentioning
confidence: 99%
“…In other words, they have an impact on input processing, which in turn has an impact on what individuals potentially comprehend. Consequently, it can be concluded that facing the tense may lead individuals to stop or go blank due to the anxiety they feel (Chen & Hwang, 2022;Daymiel et al, 2022;Giray et al, 2022;Krashen, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…One area that might cause a problem for lower Welsh language ability FLEs is speaking the Welsh language in front of more fluent peers and teachers. In this regard, language anxiety and speaking abilityparticularly with regard to vocabulary and comprehensionare significantly correlated with one another (Daymiel et al, 2022). In essence, lower language ability students' fears occur whenever they are required to speak in front of their peers, with their fear attributed to feelings of linguistic incompetence (Daymiel et al, 2022).…”
Section: 4discussionmentioning
confidence: 99%
“…In this regard, language anxiety and speaking abilityparticularly with regard to vocabulary and comprehensionare significantly correlated with one another (Daymiel et al, 2022). In essence, lower language ability students' fears occur whenever they are required to speak in front of their peers, with their fear attributed to feelings of linguistic incompetence (Daymiel et al, 2022). In this context, the fear of speaking in public is an expression of social anxiety (Alamer & Almulhim, 2021).…”
Section: 4discussionmentioning
confidence: 99%
See 1 more Smart Citation